The effect of food sensory experience on tourist engagement behavior: A study based on mental imagery theory - Sen Yang; Yi Liu; Liping Xu (PLoS ONE, 2026)
Research on the effect of food tourism on tourist engagement behavior is an important gap in tourism research. Based on mental imagery theory, this study constructed a theoretical model to explore how food sensory experience influences tourist engagement behavior, with food memory (stored multisensory experiences of food) and mental imagery (active cognitive reconstruction of sensory information) as parallel mediating variables. This is the first study to integrate mental imagery theory into food tourism research, focusing on the core role of multisensory experience. A cross-sectional online survey was conducted targeting tourists who participated in Zibo’s food tourism (Shandong, China)—a typical case of post-epidemic tourism recovery driven by food—and 447 valid questionnaires were collected. Structural equation modeling (SEM) with bootstrapped indirect effects (sample size = 5000, 95% confidence interval) was used for data analysis. Results show that: (1) Food sensory experience (encompassing sight, smell, taste, and touch) exerts a significant positive effect on tourist engagement behavior, with the strongest impacts on feedback intention (β = 0.480, p < 0.001) and revisit intention (β = 0.411, p < 0.001); (2) Food memory and mental imagery play significant parallel mediating roles—sensory experience independently activates both constructs, which in turn drive engagement; (3) Mental imagery has a stronger mediating effect on recommendation intention than food memory, while food memory is more impactful on revisit intention. Theoretically, this study clarifies the sensory-cognitive-behavioral mechanism underlying tourist engagement, filling the gap of how multisensory experiences shape engagement behavior. Practically, it provides actionable strategies for tourism destinations to enhance tourist engagement. In addition, the implications and suggestions for future research are discussed and meaningful implications for relevant tourism destinations are provided.